Archetypes and the ‘Impoverished Genome’ Argument: Updates from Evolutionary Genetics - Goodwyn, Erik (Journal of analytical psychology, 2020)
Throughout his career, Jung felt the psyche had ‘ancestral layers’ that contained elements of an individual's species history, and clinical experience has shown that this idea can be an aid to psychological healing and emotional well-being. Thus, some later thinkers have attempted to link such theoretical constructs to the genome, as Jung had little knowledge of genetics in his day. But in the early 2000s, genome studies suggested that the genome might contain too little content to be capable of encoding symbolic information. This opinion gave rise to an oft-repeated ‘impoverished genome’ argument, i.e. that the genome could not provide a significant contribution to the collective unconscious, prompting theorists to propose other sources for it, or to argue that it doesn't exist. Today, however, developments in evolutionary neurogenetics calls the impoverished genome argument into question for a number of independent reasons. These developments re-open the idea that the genome may be worth reconsidering as the biological substrate for the collective unconscious.